Mitigation of Sosial Conflict in the Implementation of the 2024 Simultaneous Regional Elections in Bogor Regency - Elfito, Fidya Arzita; Rahmawati, Rita; Apriliyani, Neng Virly (Universitas Negeri Gorontalo, 2025)
This study aimed to determine how social conflict mitigation was implemented in the 2024 Simultaneous Regional Elections in Bogor Regency, including identifying obstacles and efforts from various related institutions. The background of this study was based on the high potential for election vulnerability in West Java Province based on the Election Vulnerability Index (IKP) of Bawaslu RI, with Bogor Regency categorized as moderately vulnerable. This study used a quantitative descriptive method with a disproportionate stratified random sampling technique for employees and simple random sampling for the community, with 145 respondents. Data were collected through literature studies, observations, interviews, documentation, and questionnaires and analyzed using the Weight Mean Score (WMS) method based on the seven dimensions of the Collaborative Conflict Resolution theory. The results of the study showed that social conflict mitigation was categorized as